2011
DOI: 10.1093/molehr/gar039
|View full text |Cite
|
Sign up to set email alerts
|

Role of zonadhesin during sperm–egg interaction: a species-specific acrosomal molecule with multiple functions

Abstract: Sperm-zona adhesion is an essential event in mammalian fertilization, failure of which causes sterility. However, the molecular mechanisms involved in this process are still poorly understood. It has been suggested by few laboratories studying gamete interaction that acrosomal molecules are implicated in sperm -zona pellucida adhesion prior to the acrosome reaction (AR). Zonadhesin, a spermspecific protein located in the acrosome is critically involved in zona binding. Here we describe the cellular and molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 63 publications
(75 reference statements)
2
28
0
Order By: Relevance
“…However, the molecular mechanism of zonadhesin exposure during capacitation is not yet fully understood. 9 In summary, research on gamete interaction and AR is entering a fascinating new era. The study performed by Jin et al 1 and supported by other 7 represents a major advance in sperm physiology.…”
mentioning
confidence: 99%
“…However, the molecular mechanism of zonadhesin exposure during capacitation is not yet fully understood. 9 In summary, research on gamete interaction and AR is entering a fascinating new era. The study performed by Jin et al 1 and supported by other 7 represents a major advance in sperm physiology.…”
mentioning
confidence: 99%
“…Tardif et al [34] proposed a model in which sperm could be transiently exposed to acrosomal molecules that adhere to the zona independent from the AR in a 'kiss and run' mechanism. They concluded that this could be important for further investigations and a detailed understanding of the molecular events during sperm-ovum binding is likely to provide new approaches for the design of more effective male contraceptives and better diagnostic methods for sperm dysfunction.…”
Section: Role Of Zonadhesin During Sperm-ovum Bindingmentioning
confidence: 99%
“…They concluded that this could be important for further investigations and a detailed understanding of the molecular events during sperm-ovum binding is likely to provide new approaches for the design of more effective male contraceptives and better diagnostic methods for sperm dysfunction. [34] Acrosome reaction Sperm binding to the ZP triggers the hydrolyzing enzymes known as AR (Figure 4) and only acrosome-reacted spermatozoa can penetrate ZP, bind the oocyte membrane and fuse with oocyte. [35] The release of lytic enzymes and the presence of membrane receptors are required for the acrosome reaction, resulting in penetration of sperm through ZP and integration with the oolema.…”
Section: Role Of Zonadhesin During Sperm-ovum Bindingmentioning
confidence: 99%
“…They propose a "selective" antigen sequestration model. Nonsequestered antigens, such as testis-specific lactate dehydrogenase (Marsh et al, 1981), are protected by systemic tolerance, whereas sequestered, immunogenic antigens such as zonadhesion (Wheeler et al, 2011;Tardif and Cormier, 2011) are the major promoters of sperm autoimmunity and would dominate in a postvasectomy immune response (Table 1).…”
Section: Under What Conditions Do Men Develop Autoimmunity To Sperm?mentioning
confidence: 99%